Modern software engineering : continuous delivery and microservices with .NET (MeasureUP Conference). (Sams, 2016)
"Modern Software Engineering: Continuous Delivery and Microservices with .NET is a video compilation of the MeasureUP 2016 conference in Austin, Texas. MeasureUP aims to allow attendees to deliver custom business software of high-quality with great speed. The conference covers topics from methodology and process to deep dives into the most relevant Microsoft platform technologies. The three conference tracks--Business, Development, and DevOps--focus on how to provide custom business software with a competitive advantage. MeasureUP is an informative, educational conference with more than 11 sessions from well-known and respected professionals and MVPs."--Resource description page.